THE LEVEL OF FEELING OF HAPPINESS AMONG NURSES STUDYING AT THE DEPARTMENT "NURSE WITH HIGHER EDUCATION" AT THE CENTER FOR ADVANCED TRAINING OF MEDICAL WORKERS - Rikhsi Kamilovna Solikhodzhaeva; Jamilakhon Erkinovna Kamilova (International Scientific and Current Research Conferences, 2021)
The article examines the level of happiness among nurses studying at the Department of Nursing with Higher Education at the Center for Advanced Training of Medical Workers.